IMPLEMENTASI KEBIJAKAN SEKOLAH DALAM MENANGGULANGI KENAKALAN REMAJA DI SMA MUHAMMADIYAH 9 RAWABENING OKU TIMUR - Daliana, Rasmi; Rasyid, Abdul (Graduate Program Magister Manajemen Pendidikan, 2018)
This study aimed at describing 1) implementation of school policy in tackling juvenile delinquency in SMA Muhammadiyah 9 Rawabening; 2) supporting and inhibiting factors in implementing school policy implementation. This research is qualitative research. This research was conducted in SMA Muhammadiyah 9 Rawabening with research subjects is headmaster, student, teacher, and class guardian. Data collection techniques were interview, observation and document study. Data analysis technique using Miles and Hubberman interactive model. The results showed that 1) implementation of school policy in tackling delinquency teenagers composed in curative countermeasures in the form of socialization provided from the Department of Education of South Sumatra; Police; as well as the National Narcotics Agency. Representative efforts in the form of school rules that are applied in everyday life and must be obeyed by learners. Preventive efforts include reprimands for students who violate school rules. 2) supporting factor was high commitment of all school residents and parents, relationships are woven, and active participation of all parties. Inhibiting factors were resources that are not optimal, differences in inter-educator handling, and less strict punishment.